The effects of body position and actual execution on motor imagery of locomotor tasks in people with a lower-limb amputation - Arnaud Saimpont (Nature Portfolio, 2021)
Abstract Motor imagery (MI) is usually facilitated when performed in a congruent body position to the imagined movement, as well as after actual execution (AE). A lower-limb amputation (LLA) results in important structural and functional changes in the sensorimotor system, which can alter MI. In this study, we investigated the effects of body position and AE on the temporal characteristics of MI in people with LLA. Ten participants with LLA (mean age = 59.6 ± 13.9 years, four females) and ten gender- and age-matched healthy control participants (mean age = 60.1 ± 15.4 years, four females) were included. They performed two locomotor-related tasks (a walking task and the Timed Up and Go task) while MI times were measured in different conditions (in congruent/incongruent positions and before/after AE). We showed that MI times were significantly shorter when participants imagined walking in a congruent-standing position compared to an incongruent-sitting position, and when performing MI after actual walking compared to before, in both groups. Shorter MI times in the congruent position and after AE suggest an improvement of MI’s temporal accuracy (i.e. the ability to match AE time during MI) in healthy individuals but not in the LLA group.